2019
DOI: 10.1007/s00704-019-02926-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of urban land cover data uncertainties on the numerical simulations of urbanization effects in the 2013 high-temperature episode in Eastern China

Abstract: Updating the urban land cover information has been proved a necessary method for the numerical studies of urban climate and urban atmospheric environment in China, a fast urbanizing country. However, there are uncertainties in the urban land use/cover (ULUC) information in different datasets due to the uncertainties in raw data sources and produce methods. In this study, the Weather Research and Forecasting model is used to simulate the summer climate over the Yangtze River Delta in July and August 2013, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This index has been recommended by many official administrations such as the NOAA National Weather Service (https://www.wpc.ncep.noaa.gov/heat_index.shtml). It has also been widely used in many climate studies in China (Luo and Lau, 2018;Wang et al, 2019aWang et al, , 2019bZhang et al, 2019).…”
Section: Heat Indexmentioning
confidence: 99%
“…This index has been recommended by many official administrations such as the NOAA National Weather Service (https://www.wpc.ncep.noaa.gov/heat_index.shtml). It has also been widely used in many climate studies in China (Luo and Lau, 2018;Wang et al, 2019aWang et al, , 2019bZhang et al, 2019).…”
Section: Heat Indexmentioning
confidence: 99%
“…Over the past few decades, the rapid development of geographic information technology based on satellite remote sensing has formed multiple sets of high‐resolution global land‐use data sets, allowing extensive research on land use and land cover, including urbanization, and its influence on the weather and climate (Di Vittorio et al., 2018; Miao et al., 2009; Oleson et al., 2004). Previous studies showed that the land‐atmosphere interaction is sensitive to land‐use information (Cheng et al., 2013; Monaghan et al., 2014; Schultz et al., 2016; N. Zhang et al., 2019), which suggests that it is crucial to pay more attention to the accurate characterization of land use and land cover, such as urban lands and vegetation‐covered lands, for numerical simulations. However, numerous studies have emphasized that there are currently noteworthy disagreements among various land‐use data sets.…”
Section: Introductionmentioning
confidence: 99%
“…(Broxton et al, 2014). This is the default dataset for the version of the WRF-ARW model used here (Zhang et al, 2019).…”
Section: Study Region Experimental Setup and Model Domainsmentioning
confidence: 99%